Fire Drill Performance Evaluation Model Onboard RoRo Passenger Ship - Suwasono, Bagiyo; Sudirman,; Gunawan, Fajar (International Journal of Marine Engineering Innovation and Research, 2025)
Fire accident onboard RoRo (Roll on/Roll off) passenger ferry notoriously indicates intense symptoms of human, technical and organisational issues. In some cases, the more complex the fire's origin, the more challenging the crew would handle handling, suppressing, and putting out the fire. The crew response plays a significant role in the success of firefighting onboard. The research focuses on evaluating the effectiveness of fire drill performance by developing an evaluation model based on the cognitive model and analytical network process. The model was developed to overview crew performance and consistency in conducting fire drills on board the roro passenger ship. The questionnaire is developed to obtain crew perspective and awareness of fire risks. The analytical network process (ANP) model is utilised to identify crew preference during fire drills. The result of decision-based research identified significant issues that occurred in every step of cognition. Competency and proficiency of the crew, along with continuous training and familiarisation, were the main issues in improving effectiveness in firefighting. The results of the analysis were resourceful evidence to enhance audit and supervision for the emergency preparedness system. In addition, it is also a reference for developing further training models to improve crew overall performance in firefighting.